Vapor-phase oxidation of ethylene glycol methanolic solution into methyl glycolate over CuO-containing catalysts - Varvarin, Anatolii M.; Levytska, Svitlana I.; Mylin, Artur M.; Zinchenko, Oleksii Yu.; Brei, Volodymyr V. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2022)
The gas-phase oxidation of ethylene glycol and methanol mixture into methyl glycolate С2H6O2+CH3OH+O2 = C3H6O3+2H2О over synthesized copper-containing catalysts was studied. Methyl glycolate can be considered as raw material for obtaining biodegradable polyglycolide. The CuO-containing samples were synthesized by impregnation of granular oxide-supports (γ-Al2O3, SiO2 and MgO-ZrO2) with the calculated amount of aqueous solution of Cu(NO3)2·3H2O followed by heat treatment at 400 °C. In such way the supported CuO-MexOy /Al2O3 (Me = Mg, Ti, Cr, Co, Zn, Zr, Ag) samples have been prepared. Catalytic experiments were performed in a stainless-steel flow reactor with a fixed bed of catalyst at 200-270 °C and atmospheric pressure. Oxygen of air was used as an oxidant. The reaction products were analyzed using 13C NMR spectroscopy and gas chromatography. It was found that СuO/Al2O3 catalyst provides ~ 100% ethylene glycol conversion with 56% selectivity towards methyl glycolate at 220 °С. The main by-products are methoxymethanol, 1,1-dimethoxymethane, methyl methoxyacetate, and methyl formate. Use of silica as catalyst support leads to a significant decrease of the ethylene glycol conversion to 57 % for CuO/SiO2, but methyl glycolate selectivity does not change significantly. Promotion of СuO/Al2O3 with MgO increases methyl glycolate yield to 64%. According to the scheme of ethylene glycol sequential oxidation the increase in selectivity for methyl glycolate over CuO-MgO/Al2O3 catalyst is caused by the basic sites that promote intramolecular Cannizzaro rearrangement of the intermediate reaction product – glyoxal hemiacetal to methyl glycolate. It’s found that mixed CuO-CrO3 oxide supported by γ-Al2O3 provides 80 % methyl glycolate selectivity with 95-100% ethylene glycol conversion at 200-210 °C.